Towards class arbitration in the consumer law in Colombia. A reference to the AT&T mobility llC v. Concepcion case (2021)
This article highlights a new discussion in Colombia, that is, the role that arbitration could play in consumer law. The paper also analyses a signature case in U.S. arbitration consumer law (AT&T Mobility v Concepcion), which offers the basis to open the debate of small claims contested during a Class Arbitral proceeding. It also weighs on the legal nature of Class Waiver Clause. It furthers on the possible sanctions that could be imposed on that clause, to conclude that Consumer Law in Colombia deserves a better and effective procedure favoring consumers by voiding with inefficacy a possible Class Waiver in an arbitration agreement